Pengaruh Kinerja Keuangan Terhadap Return Saham (Studi Pada Emiten Saham Syariah Sektor Manufaktur Yang Terdaftar di Indeks Saham Syariah Indonesia Tahun 2011-2012) - Roslianti, Rizkary; Herlambang, Leo (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Islamic stocks is one of the most preffered investment type by Muslim investors. In the decision making process, the investors have to considered the financial reports and stock analysis. This study aims to investigate the effect of fundamental factors that represented by Return on Assets, Debt to Equity Ratio and Total Assets Turnover toward stock return.This study used a quantitative approach using secondary data, they are financial statements and stock return companies listed on Indeks Saham Syariah Indonesia years 2011-2012. This study used a significance level of 5%.Based on the regression analysis results, it indicates that Return on Assets variable has a very significant effect on the stock return. On the other hand, Debt to Equity Ratio variable and Total Assets Turnover variable do not have significant effect to the stock return. Simultaneously, Return on Assets, Debt to Equity Ratio and Total Assets Turnover have significant effect to stock return.